PENGARUH POLA ASUH ORANG TUA TERHADAP KEDISIPLINAN DAN HASIL BELAJAR AL ISLAM SISWA KELAS III SD MUHAMMADIYAH 01 BANGKALAN (PIONIR: JURNAL PENDIDIKAN, 2023)
The Indonesian nation is a nation that is rich in human resources. To provide Contributitons to the nation, we need to give something to our country, one of which is high education this is education has also been regulated in the Constitution, it is important for us to have a high education. Therefore, this research is also for the tield of education, especially primary education. This study aims to determine the effect of parenting on the discipline and learning outcomes the third grade students of SD Muhammadiyah 01 Bangkalan. This study uses a quantitative type of research while the design uses a non-experimental because there is no treatment in this study. In this study, the researcher used a parent response questionnaire, a student response questionnaire, and test questions for students aimed at knowing student learning outcomes. The results of this study can be concluded that based on the results of a simple linear regression test seen from a significance value of less than 0.05. The influence between variables x and y. In this study is a sig value of 0.000, therefore it is said to have an effect between variables x and y.
Keywords: Education; Parenting; Discipline; Quantitative; Students.